A cost-effectiveness analysis of subcutaneous interferon beta-1a 44mcg 3-times a week vs no treatment for patients with clinically isolated syndrome in Sweden. (June 2013) - Fredrikson, Sten; McLeod, Euan; Henry, Nathaniel; Pitcher, Ashley; Lowin, Julia; Cuche, Matthieu; Fajutrao, Liberty; Perard, Rodolphe; Bates, David; Chan, Andrew
Abstract Objective: To assess the cost-effectiveness of subcutaneous interferon (sc IFN) beta-1a 44 mcg 3-times weekly (tiw) vs no treatment at reducing the risk of conversion to multiple sclerosis (MS) in patients with clinically isolated syndrome (CIS) in Sweden. Methods: A Markov model was constructed to simulate the clinical course of patients with CIS treated with sc IFN beta-1a 44 mcg tiw or no treatment over a 40-year time horizon. Costs were estimated from a societal perspective in 2012 Swedish kronor (SEK). Treatment efficacy data were derived from the REFLEX trial; resource use and quality-of-life (QoL) data were obtained from the literature. Costs and outcomes were discounted at 3%. Sensitivity analyses explored whether results were robust to changes in input values and use of Poser criteria. Results: Using McDonald criteria sc IFN beta-1a was cost-saving and more effective (i.e., dominant) vs no treatment. Gains in progression free life years (PFLYs) and quality-adjusted life-years (QALYs) were 1.63 and 0.53, respectively. Projected cost savings were 270, 263 SEK. For Poser criteria cost savings of 823, 459 SEK were estimated, with PFLY and QALY gains of 4.12 and 1.38, respectively. Subcutaneous IFN beta-1a remained dominant from a payer perspective. Results were insensitive to key input variation. Probabilistic sensitivity analysis estimated a 99.9% likelihood of cost-effectiveness at a willingness-to-pay threshold of 500, 000 SEK/QALY. Conclusion: Subcutaneous IFN beta-1a is a cost-effective option for the treatment of patients at high risk of MS conversion. It is associated with lower costs, greater QALY gains, and more time free of MS. Limitations: The risk of conversion from CIS to MS was extrapolated from 2-year trial data. Treatment benefit was assumed to persist over the model duration, although long-term data to support this are unavailable. Cost and QoL data from MS patients were assumed applicable to CIS patients.